Deportacje internowanych Polaków z województwa białostockiego 1944–1945 - Zwolski, Marcin (Pamięć i Sprawiedliwość, 2005)
Most of the Poles deported in years 1944 and 1945 from the province of Bialystok were internees – people incarcerated without charges or trial for an indefinite period of time. It affected particularly those having connections with the Polish Underground Movement, mainly the Home Army (AK). Detained and deported were also people who were accused of collaboration and those who accepted German citizenship during the war.What helped the UB to expose the underground movement and dismantle its structure was an operation with a codename “Tempest” carried out by the Home Army itself. Under the operation members of the civil and military conspiracy, subordinated to the Polish government, revealed themselves to the entering Soviet soldiers.Deportations of the internees were conducted by the Soviet Political Police – NKWD and the military counterintelligence – Smiersz. However, in the Bialystok province, they were actively supported by functionaries of the Polish security apparatus (UB). While in the other territories of Eastern Poland (Polska Lubelska) the UB arrested only individuals, in Bialystok it surrendered 900 people to the Soviets. It constituted almost 20 per cent of the total number deported from the whole of Bialostocczyzna.From August 1944 to February 1945 about 5000 people were taken to the detention camps in the USSR, 3300 of them had been related to the Polish underground conspiracy. The greatest number of deportations occured in November 1944, when there were higher rank officers of the Soviet security in Bialystok – Wiktor Abakumov and Lavrientij Canava. They supervised a three-week long operation under which 2900 people were arrested and deported to the Ostaszkov camp. Destinations of the others deported from Bialostocczyzna were camps in Stalinogorsk, Charkov and Riazan.